Cloud Computing Model for MyGRANTs Project - Fakhreldin, Mohammed Adam Ibrahim; Jasni, Mohamad Zain; Abdalla, Ahmed N.; Mohamad Fadli, Zolkipli; Ramdan, Razali (2013)
Abstract. Key management is the most complex part of any security system dealing with encryption of data. Using cloud computing reduces not only pressure on IT cost but it provides satisfactory performance. However, a very fundamental issue on cloud computing is the loss of hands-on control of system, application, and data security. In viewing of current cloud-computing environment, there is an issue of a comprehensive key management scheme. This paper analyzes the special security requirements of key management under the cloud-computing environment. The study involves analyzing a cloud-computing key management framework based on the XML key management specification and designs the cloud-computing key management framework and module function for MyGRANTs. XML key management specification establishes an abstraction layer between the application program and PKI, which solves the interoperability problem between different PKI systems. As a result, the improved interoperabilty of cloud computing key management with three working modules based on different trust relationship for MyGRANTs is outlined.